A Compact 3.1- 18.8 GHz TripleBandNotchedUWB Antennafor mobileUWB Applications - Devana, V N Koteswara Rao; Rao, A. Maheswara (IRO Journal on Sustainable Wireless Systems, 2020)
A compact triple band notched tapered microstrip fed Ultrawideband (UWB) antenna for wireless communication applications in C, X and Ku bands is proposed. The antenna having a compact size of 16Ã—26 mm2 , consisting of an elliptical patch and a truncated ground structure to achieve impedance of -10 dB bandwidth of 3.1 GHz to 18.8 GHz. Triple band notched characteristics are obtained from 3.7 GHz to 4.2 GHz for C band, 5.18 GHz to 5.85 GHz for Wireless Local Area Network (WLAN) and 8 GHz to 8.4 GHz for X band applications associated with the satellite communication, fabricating three inverted slots that are U-shaped in the patch of elliptical form. Good agreement between theoretical and the practical results achieved through simulation of the antenna proposed is a compatible candidate for portable ultra-wide band applications.